Comparison Study of Wide Bandgap Polymer (PBDB-T) and Narrow Bandgap Polymer (PBDTTT-EFT) as Donor for Perylene Diimide Based Polymer Solar Cells - Ye, Tengling; Jin, Shan; Kang, Cong; Tian, Changhao; Zhang, Xin; Zhan, Chuanlang; Lu, Shirong; Kan, Zhipeng (Frontiers in Chemistry, 2018)
Perylene diimide (PDI) derivatives as a kind of promising non-fullerene-based acceptor (NFA) have got rapid development. However, most of the relevant developmental work has focused o on synthesizing novel PDI-based structures, and few researchers have paid attention to the selection of the polymer donor in PDI-based solar cells. Wide bandgap polymer (PBDB-T) and narrow bandgap polymer (PBDTTT-EFT) are known as the most efficient polymer donors in polymer solar cells (PSCs). While PBDB-T is in favor with non-fullerene acceptors achieving power conversion efficiency (PCE) more than 12%, PBDTTT-EFT is one of the best electron donors with fullerene acceptors with PCE up to 10%. Despite the different absorption profiles, the working principle of these benchmark polymer donors with a same electron acceptor, specially PDI-based acceptor, was rarely compared. To this end, we used PBDB-T and PBDTTT-EFT as the electron donors, and 1,1′-bis(2-methoxyethoxyl)-7,7′-(2,5-thienyl) bis-PDI (Bis-PDI-T-EG) as the electron acceptor to fabricate PSCs, and systematically compared their differences in device performance, carrier mobility, recombination mechanism, and film morphology.